Overexpression of SOX4 in MSCs inhibits cellular senescence and enhances therapeutic efficacy in systemic lupus erythematosus - Jingjing Qi; Xiangge Zhao; Xiaoyu Gao; Xiaolu Zhu; Junli Wang; Jiaqing Liu; Jing Wei; Xia Li; Bihu Gao (Stem Cell Research & Therapy)
Abstract Background Mesenchymal stem cells (MSCs) are widely used in treating autoimmune diseases. However, replicative senescence limits the quantity and quality of MSCs during population doublings in vitro. Transcription factor SOX4 is a crucial regulator of cell fate and stemness. This study aims to explore the role of SOX4 in senescence of MSCs and enhance their therapeutic efficacy in systemic lupus erythematosus (SLE). Methods In early-passage MSCs (P3), late-passage MSCs (P8), SOX4 downregulated P3-MSCs or SOX4 overexpressed P8-MSCs, cell morphology, mitochondrial reactive oxygen species (mtROS), senescence-associated β-galactosidase (SA-β-Gal) activity, cell proliferation rate, senescence-associated secretory phenotype (SASP) factors, cell cycle suppressors, the immunosuppressive effects on T cell activation and proliferation and the expression levels of SOX4 were determined. Imiquimod induced SLE mice were transplanted with P3-MSCs and P8-MSCs or control and SOX4 overexpressed P8-MSCs, and clinical symptoms were assessed. Results Compared to P3-MSCs, P8-MSCs display a senescent phenotype, increased mtROS, SA-β-Gal activity, SASP factors, and cell cycle suppressors p53, p21, and p16. Additionally, P8-MSCs have a reduced immunosuppressive function on T cell activation and proliferation, and express lower levels of SOX4. Downregulation of SOX4 in P3-MSCs promotes cellular senescence and impairs their immunosuppressive function. Conversely, overexpression of SOX4 in P8-MSCs ameliorates cellular senescence and enhances their immunosuppressive function. Furthermore, transplantation of P3-MSCs or SOX4-overexpressing P8-MSCs demonstrates greater therapeutic significantly efficacy in SLE mice compared to P8-MSCs. Conclusions Taken together, these findings suggest that downregulation of SOX4 induces senescence in MSCs and impairs their immunosuppressive function. Targeting SOX4 in MSCs may therefore represent a promising therapeutic approach for the treatment of SLE.